Quality of soybean sowing as a function of the speed of the sowing tractor and seed metering disk (Research, Society and Development, 2021)
The precision seeders are submitted to different working conditions, which can cause variation in the spatial distribution of seeds in the sowing line. The objective of this work was to evaluate the quality of the sowing of the soybean crop as a function of the advance speed of the tractor-seeder and of the seed dosing disc, in no-tillage. The experimental design was completely randomized, with 10 treatments in a 5x2 factorial scheme, composed of five forward speeds of the tractor-seeder-fertilizer (3, 4, 5, 6 and 7 km h-1) and two seed dosing discs (40 and 108 alveoli), with five repetitions per treatment. The number of days for emergence, sowing depth, initial and final stand, longitudinal distribution of plants, plant height and insertion of the first pod, productivity and mass of a thousand grains were evaluated. The increase in sowing speed influenced the reduction in the percentage of acceptable spacing, and consequently, the percentage of double and flawed spacing increased. However, the displacement speeds did not influence the productivity and mass of a thousand grains, producing an average of 5017.46 kg ha-1 and 168.89 g, respectively. The disk with 108 wells showed a higher percentage of acceptable spacing and a greater mass of a thousand grains, but did not influence grain yield. In the studied conditions, the speed of 7 km h-1 and the disk of 108 alveoli are indicated, aiming at a better operational field capacity.